Deafblind Olympics: A case for a grand challenge - Schatoff, O. (Procedia Engineering, 2012)
This paper proposes a Grand Challenge to serve as the impetus for the reexamination of sports and sports technology under the prism of enabling elite deafblind participation to foster innovation in sports engineering. Technical obstacles faced by deafblind athletes are classical engineering challenges: on-field positioning, path-following navigation, range finding, collision detection, peer-to-peer communication and object identification (friend or foe). Sufficient technical progress has been achieved to allow for robots to compete in the game of soccer (Robocup), similar progress can be put forth for the development of elite deafblind athletics. A collaborative effort to solve the Grand Challenge of the Deafblind Olympics has the potential for spurring innovation in sports training, sports equipment and stadium design. This paper presents a survey of various technical challenges faced by the elite deafblind athlete.